Psychiatry Registry of Pakistan: The First National Registry on Psychiatric Disorders in Pakistan-Concept Note - Soomro, Marium; Ahmed, Zakiuddin; Noor, Syed Shahid (Journal of Pakistan Psychiatric Society, 2024)
Not applicable